2001
DOI: 10.4064/fm170-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Ordered group invariants for one-dimensional spaces

Abstract: Abstract. We show that the Bruschlinsky group with the winding order is a homeomorphism invariant for a class of one-dimensional inverse limit spaces. In particular we show that if a presentation of an inverse limit space satisfies the Simplicity Condition, then the Bruschlinsky group with the winding order of the inverse limit space is a dimension group and is a quotient of the dimension group with the standard order of the adjacency matrices associated with the presentation. Introduction.Ordered groups have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In recent developments, ordered group invariants in C * -algebras and topological dynamics have been used to provide invariants of homeomorphisms of certain one-dimensional compact metrizable spaces ( [1], [2], [3], [6], [9], [10], [11], [16]). We can interpret these results as follows: the firstČech cohomology group of the space is given a preorder, and the isomorphism class of the resulting preordered group becomes an invariant of the homeomorphism class of the space.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent developments, ordered group invariants in C * -algebras and topological dynamics have been used to provide invariants of homeomorphisms of certain one-dimensional compact metrizable spaces ( [1], [2], [3], [6], [9], [10], [11], [16]). We can interpret these results as follows: the firstČech cohomology group of the space is given a preorder, and the isomorphism class of the resulting preordered group becomes an invariant of the homeomorphism class of the space.…”
Section: Introductionmentioning
confidence: 99%
“…Every 1-solenoid has an elementary presentation ( [14], [15]). If (X, f ) is an elementary presentation of a 1-solenoid X and M = M X,f is the adjacency matrix of f : X → X, theň H 1 (X) is isomorphic to ∆ M ( [16]). This invariant of the homeomorphism class of X was refined by Jacklitch ( [3]), who showed that if (X, f ) and (Y, g) are elementary presentations of oriented 1-solenoids X and Y , then the dimension groups…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the matter of canonical symbolic dynamics, we mention renewed interest in Williams' systems and related systems on account of connections with ordered group invariants ( [3,12,18]) and substitutions and tilings ( [2,6]).…”
mentioning
confidence: 99%